Analysis of The Effect of Price Discount On Technology Perceived Quality, Technology Perceived Value and Perceived Savings on Intention To Use Digital Payment Application Gopay - Butar Butar, Ribka Sari; Dharmawan, Donny; Amelia, Deni; Musdirwan; Nuryanto, Uli Wildan (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to examine how consumers' purchase intentions are affected by price discounts by examining how they are regarded to be beneficial, valuable, and high-quality. This study used a conclusive research design and a descriptive research type, and it was quantitative in nature. This study employs a single cross-sectional design so each sample will be sampled just once. The target population for this study was everyone who had done retail shopping. There were 100 samples used in this investigation. Online questionnaires were distributed by researchers in order to gather data. Researchers processed pre-test data using SPSS and factor analysis. Research leads one to the following conclusions on the study's findings: Discounts on prices positively impact the perceived savings. Discounts in price have a detrimental effect on the perceived quality. Price reductions positively impact other price reductions. Discounts in price positively impact the perceived savings. Discounts in price positively impact the perception of quality. Perceived value is positively influenced by the price reduction effect. In terms of perceived savings, perceived quality, and perceived value, the price discount influences the mediator and positively effects price discounts. Perceived value is positively impacted by perceived savings. Perceived value is positively impacted by perceived quality. Purchase intentions are positively impacted by perceived value.